IDENTIFICATION OF TAXPAYERS IN ELECTRONIC COMMERCE - Karimova Nilufar Bobir qizi (PT. Antis International Publisher, 2024)
E-commerce activities differ from traditional commerce in that they are not located at a specific address, which, while convenient for the seller and customer, creates difficulties for the state in determining the taxpayer, tax object, and tax base. Therefore, identification of taxpayers in e-commerce is one of the primary tasks of the state and direct tax authorities today.